(untitled) (Research, Society and Development, 2021)
Objective: The aim of this study was to evaluate the use of antimicrobials in elderly people admitted to a public hospital. Methodology: This is a cross-sectional study, quantitative and descriptive, carried out in the Medical Clinic of a public hospital in Bahia, over a period of three months, using a form structured by the researcher. Forty-two medical records of patients aged over 60 years were analyzed. Of these, 29 were using antimicrobials. Results: The prevalence of TMJ use was (69%), being higher in females (93%) and in patients aged 80 years or older (52%). The most used drugs were ceftriaxone (59%), levofloxacin (28%) and azithromycin (28%). There was a predominance of polypharmacy (100%). In addition, the main diagnoses for the use of TMJs were for diseases that affect the respiratory system (38%) and diseases of the circulatory system (32%). Regarding the route of administration, the highest frequency of use of the intravenous route was observed (79%). Conclusion: It is suggested that it is necessary to know the use of these drugs in hospitals, especially in geriatrics, to support the development of clinical protocols, reduce treatment by empirical therapy, in addition to the importance of the interaction of the multidisciplinary team to avoid the increase in resistance bacterial and prevent as much as possible prescriptions from occurring.